2018
DOI: 10.1016/j.otsr.2018.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Bone and parietal anterior iliac crest reconstruction for trans-iliac hernia after tricortical graft harvesting: An original technique

Abstract: Tricortical cortico-cancellous bone allografts from the anterior iliac crest are routinely used in revision arthroplasty and to treat non-union. Trans-iliac herniation (TIH) has been reported as an exceptional complication after extensive graft harvesting. The various reconstruction techniques include isolated parietal reconstruction and combined parietal and bone reconstruction using allografts or a spacer to reconstruct the bone defect. No previous study has evaluated a combined reconstruction technique invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Studies have shown that reconstructing iliac crest defects after autogenous harvesting with bone cement and cancellous screws can reduce postoperative pain and improve cosmesis [ 18 ]. A study of surgical repair of hernias after tricortical iliac bone harvesting showed that reconstruction of the ilium with a titanium plate followed by peritoneal repair with partially absorbable mesh and fixation of the mesh to the titanium plate was effective in the treatment of hernias after tricortical iliac bone harvesting [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that reconstructing iliac crest defects after autogenous harvesting with bone cement and cancellous screws can reduce postoperative pain and improve cosmesis [ 18 ]. A study of surgical repair of hernias after tricortical iliac bone harvesting showed that reconstruction of the ilium with a titanium plate followed by peritoneal repair with partially absorbable mesh and fixation of the mesh to the titanium plate was effective in the treatment of hernias after tricortical iliac bone harvesting [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The traditional open “U” bone extraction, although effective for obtaining a large amount of cancellous and cortical bone, inevitably result in complications, such as permanent bone loss, herniation in the donor area, residual cosmetic deformity, nerve damage, and local pain. Materials used to repair iliac bone defects include screws and PMMA, a flexible titanium craniofacial reconstruction plate, a polypropylene/poliglecaprone parietal reinforcement prosthesis, hydroxyapatite–calcium triphosphate biphasic compound, and bioactive ceramic spacers [ 17 , 18 ]. However, we believe this procedure increased surgical costs and was limited by late local loosening and permanent bone defects in the iliac region.…”
Section: Discussionmentioning
confidence: 99%
“…The anterior superior iliac spine (ASIS), anterior inferior iliac spine (AIIS), iliac tubercle, and posterior superior iliac spine (PSIS) are important surface markers for evaluating the position of the iliac crest [ 18 , 19 ]. Many soft tissues, such as the sartorius, tensor fascia lata, superficial layer iliaotibial band, gluteal aponeurotic fascia, inter- and external oblique muscles, transversus abdominis, and iliac muscle, are attached to the iliac crest [ 19 , 20 ]. In addition, there are many major nerves and arteries around the iliac crest, including the lateral femoral cutaneous nerve, ilio-inguinal nerve, ilio-hypogastric nerve, subcostalis nerve, ilio-lumbar artery, deep circumflex iliac artery, fourth lumbar artery, and superior gluteal artery [ 21 23 ].…”
Section: Methodsmentioning
confidence: 99%